Desarrollo de una propuesta de un sistema de carga interno para vehículos eléctricos - Barboza-Valverde, Javier Alonso (Instituto Tecnológico de Costa Rica, 2018)
The purpose of this project is the design of a boost converter (Boost) with correction of the power factor, which will serve as the basis for the proposal of an internal charging system of an electric vehicle, that can be implemented in future semesters. In addition, it is intended that with this project, it is possible to deliver to the Electric Vehicle Research Laboratory, a functional proposal of a charging system for an electric vehicle, so that the electric mobility of Costa Rica can be greatly impelled. In this document, the complete study of the proposed solution is presented, from the design to its simulation in real time, using the tool called MATLAB, which allows to control and approximate this project to a physical environment. As a main contribution, a correction of the power factor in the battery charge is presented, to obtain a circuit in which the use of current and voltage at the output of the system is maximized, helping in some way to improve the control of the voltage and the current with a minimum ripple. This system takes into account different stages for obtaining the charging process above 95% of the battery, using rectification of alternating current to direct current, a DC / DC converter Boost, which is able to control the voltage and current output In addition, with the use of the average current control method and power control at the output of the system, it helps to achieve a power factor of 0.99, maximizing the useful life of the battery.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Convertidores; Control; Corriente; Factores; Potencia; Tensión; Corriente; Baterías; Matlab web server; Automóviles eléctricos; Ciclos; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics